2010
DOI: 10.1093/ndt/gfq669
|View full text |Cite
|
Sign up to set email alerts
|

Dedication of a nurse to educating suboptimal haemodialysis starts improved transition to independent modalities of renal replacement therapy

Abstract: Addition of the RTN to the HD care team facilitated transition to independent modalities of RRT in suboptimal HD starts. This standardized approach to the care of such patients should be considered in HD units where suboptimal HD starts are common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 29 publications
0
55
0
1
Order By: Relevance
“…The perception of minimal impact may also relate to the absence of a formal training program to teach dialysis nurses how to educate patients. Although nephrology nurses can be effective at guiding modality selection [30-32], traditionally, the role of dialysis nurses has not primarily been patient education.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of minimal impact may also relate to the absence of a formal training program to teach dialysis nurses how to educate patients. Although nephrology nurses can be effective at guiding modality selection [30-32], traditionally, the role of dialysis nurses has not primarily been patient education.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study evaluated the effect of an in-hospital education programme among 228 patients requiring acute dialysis starts [9]. Our study shows that a sub-optimal dialysis initiation defined by a short stay on HD before starting PD was associated neither with an increased risk of death nor with a decreased probability of renal transplantation.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, it has recently been shown in a single-centre retrospective study that acute starters have a similar outcome on PD and on HD [7]. Efforts are currently made to offer a free choice of the dialysis modality to the unplanned dialysis starter [8,9]. These considerations may increase the number of patients starting PD after a short stay on HD in coming years.…”
Section: Introductionmentioning
confidence: 99%
“…The initiation of dialysis is unplanned in up to 50% of patients, and these patients typically default to in‐centre HD and are unlikely to change modalities . While patients with suboptimal HD starts are likely to incur delays to their transition to home HD, because of vascular access problems, we found that these participants also experienced immediate lifestyle benefits from home HD. To some extent, our findings support the aims of ‘home first’ initiatives, to encourage patients immediately to home HD .…”
Section: Discussionmentioning
confidence: 75%